2020
DOI: 10.1039/d0ra08203a
|View full text |Cite
|
Sign up to set email alerts
|

Rib shaped carbon catalyst derived from Zea mays L. cob for ketalization of glycerol

Abstract: In the present work, the activated carbon was derived from corncob via NaOH activation for solketal production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The band at 1620 cm –1 was assigned to the H–O–H bending vibration of absorbed water, and its signal decreased with the increase of reaction time, probably indicating the consumption of adsorbed water. The broad and intense band centered at 3372–3447 cm –1 (Figure b) was assigned to the stretching absorption of the hydroxyl bond . Several main hydroxyl-contained compounds including glycerol (3378 cm –1 ), lactate (3418 cm –1 ), formate (3448 cm –1 ), fresh Ru/ZrO 2 (3440 cm –1 ), and NaHCO 3 (3474 cm –1 ) could be responsible for this broad peak according to their ex situ FTIR spectra (Figure c).…”
Section: Results and Disscussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The band at 1620 cm –1 was assigned to the H–O–H bending vibration of absorbed water, and its signal decreased with the increase of reaction time, probably indicating the consumption of adsorbed water. The broad and intense band centered at 3372–3447 cm –1 (Figure b) was assigned to the stretching absorption of the hydroxyl bond . Several main hydroxyl-contained compounds including glycerol (3378 cm –1 ), lactate (3418 cm –1 ), formate (3448 cm –1 ), fresh Ru/ZrO 2 (3440 cm –1 ), and NaHCO 3 (3474 cm –1 ) could be responsible for this broad peak according to their ex situ FTIR spectra (Figure c).…”
Section: Results and Disscussionmentioning
confidence: 96%
“…The broad and intense band centered at 3372−3447 cm −1 (Figure 5b) was assigned to the stretching absorption of the hydroxyl bond. 36 Several main hydroxyl-contained compounds including glycerol (3378 cm −1 ), lactate (3418 cm −1 ), formate (3448 cm −1 ), fresh Ru/ZrO 2 (3440 cm −1 ), and NaHCO 3 (3474 cm −1 ) could be responsible for this broad peak according to their ex situ FTIR spectra (Figure 5c). Obviously, the peak assigned to the hydroxyl weakened and displayed a significant hypsochromic shift from 3370 to 3450 cm −1 with the increase of reaction time, corresponding to the consumption and transformation of glycerol.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…The morphology of SBPE and SBPEAC composites was analyzed through TEM, illustrated in Figure S1 . It was observed that the SBPE composite does not have any pores, whereas, after the co-carbonized of SBPE through pyrolysis, the SBPEAC composite had a porous structure [ 46 ]. Similar results were reported by Hossain et al [ 47 ] for mesoporous activated carbon developed from hemp bast fiber through hydrothermal processing.…”
Section: Resultsmentioning
confidence: 99%
“…After MG adsorption on SBPE and SBPEAC, the atomic concentration of C increased from 72.1 to 74.3% and 82.3 to 85.2%, respectively, which might be due to the accumulation of MG ions over the SBPE and SBPEAC surface. The deconvoluted C1s spectrum of SBPEAC showed peaks at 284.61, 285.1, 286.7, and 289.46 eV attributed to C-C/C=C, C-O/C-N, C=O, and O-C=O, respectively ( Figure 3 a) [ 46 , 47 ]. The high-resolution deconvoluted O1s spectrum of SBPEAC showed four peaks at 531.12, 532.51, 533.80, and 536.01 eV, which were assigned to C-O, C=O, and O-C=O, respectively ( Figure 3 b) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lower conversions were obtained in the work of J. Kaur [ 72 ] and co-workers, where value-added carbon produced from Zea mays L. cob was activated by NOH ( Figure 9 ) and used to produce solketal. The optimum conditions achieved with a molar ratio of 1:8:8 (glycerol:acetone:methanol) in 1 h with 5 wt% (w.r.t.…”
Section: Glycerol Conversion Using Biochar Catalystsmentioning
confidence: 99%